Bioactivity of the organic extracts of Annona vepretorum on Tetranychus urticae (Acari: Tetranychidae) - Fernandes, Maria Herlândia de Araújo; Menezes, Karen Oliveira de; Souza, Adriana Maria de; Almeida, Jackson Roberto Guedes da Silva; Oliveira, José Eudes de Morais; Gervásio, Rita de Cássia Rodrigues Gonçalves (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the lethal and sublethal toxicity of hexane and methanolic extracts from the leaves of Annona vepretorum (Annonaceae) on Tetranychus urticae (Acari: Tetranychidae). The methanolic extract toxicity was evaluated by Potter tower application (topical + residual effect) and by immersion of Canavalia ensiformis leaf disks in the extract solution (residual contact effect). The hexane extract toxicity was evaluated exclusively through residual contact effect. Sublethal effects of the methanolic extract were evaluated through LC50 on the females. Mite preference for feeding and oviposition was evaluated by multiple choice tests, between the control and the extract concentrations, using the hexane and methanolic extracts. Estimated LC50 for the methanolic extract was 10.96 mg mL-1 for the topic + residual effect and 22.07 mg mL-1 for the residual effect. Estimated LC50 for the hexane extract was 50.61 mg mL-1. The methanolic extract at the previously estimated CL50 interfered in the fecundity and longevity of females, differing significantly from the control treatment. In the multiple choice tests, for both extracts, mites showed a significant preference for the control, both for feeding and oviposition. Annona vepretorum has acaricide effect and constitutes a botanical source with great potential for controlling T. urticae.